The Role of Educators in Students’ Verbal Abuse and Bullying Prevention at SMP Negeri 1 Tanjung Raja Ogan Ilir District - Sherly Desliyanah; Dicky Depiansyah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The objective of this study is to investigate several facets of the role that educators play in the verbal abuse and bullying prevention of students at SMP Negeri 1 Tanjung Raja in Tanjung Raja District, Ogan Ilir Regency. The qualitative descriptive method is being used in this study. The researchers conduct observations and interviews as part of their data collection methods. There were seven informants in total for this investigation. This study is being conducted at Tanjung Raja sub-district, Jalan Sultan Mahmud Badaruddin II, in the Ogan Ilir Regency. The study's findings indicate that educators have a positive impact in educating students about bullying and how to protect themselves from various risks. In addition to this, the role of the teacher and the curriculum in the school is crucial in providing a safe and nurturing environment for the development of the students. It is anticipated that the research findings will be able to make a contribution to more effective education reform in SMP Negeri 1 Tanjung Raja and other schools.